Nonlinear Differential Equations of Monotone Types in Banach Spaces - Barbu, Viorel; SpringerLink (Online service) (New York, NY : Springer New York, 2010)
This book is concerned with basic results on Cauchy problems associated with nonlinear monotone operators in Banach spaces with applications to partial differential equations of evolutive type. This is a monograph about the most significant results obtained in this area in last decades but is also written as a graduate textbook on modern methods in partial differential equations with main emphasis on applications to fundamental mathematical models of mathematical physics, fluid dynamics and mechanics. This book is selfcontained while the prerequisites in functional analysis are necessary to understand as it is being presented in a preliminary chapter. An up-to-date list of references and extended comments are included.
Fundamental Functional Analysis -- Maximal Monotone Operators in Banach Spaces -- Accretive Nonlinear Operators in Banach Spaces -- The Cauchy Problem in Banach Spaces -- Existence Theory of Nonlinear Dissipative Dynamics.
Keywords: Mathematics; Global analysis (Mathematics).; Differential equations, partial; Mathematics; Partial Differential Equations; Analysis